Handbook of emergency response to toxic chemical releases : a guide to compliance - Cheremisinoff, Nicholas P. (Noyes Publications, 1995)
This handbook has been prepared as a working reference for the safety officer, the environmental engineer and the consultant. For the safety officer, this handbook provides guidelines and instructions in preparing Right-to-Know Reporting Audits, establishing programs and training employees on hazard awareness, and developing and implementing emergency response programs in the workplace and at off-site operations. For the environmental engineer, this handbook provides technical data on toxic chemical properties and an instructional aid on how to properly prepare toxic chemical release inventory reporting.